OPTIMIZATION OF MICROWAVE- AND ULTRASONIC-ASSISTED EXTRACTION OF MAHKOTA DEWA (PHALERIA MACROCARPA [SCHEFF.] BOERL.) FRUIT PULP - HANDAYANI, ROSITA; BANGUN, ANDRE; DEBORAH, PASKAH DEWI; MUN’IM, ABDUL (International Journal of Applied Pharmaceutics, 2020)
Objective: This work aimed to determine the optimal extraction conditions of Mahkota dewa using different extraction methods: microwave-assisted extraction with ethanol (MAE-ethanol), ultrasonic-assisted extraction using a choline chloride natural deep eutectic solvent (UAE-NADES), and Soxhlet and reflux extractions. Methods: Experimental design was performed through Box-Behnken. The efficiency of the methods was evaluated based on the total phenolic content (TPC) and antioxidant activity. The presence of relevant compounds was qualitatively assessed by high-performance liquid chromatography (HPLC). Results: For the MAE-ethanol method, optimum extraction was achieved with 65% ethanol, in 1 min under 30% microwave power, and a 1:12 sample– solvent ratio, which yielded a TPC and antioxidant activity of 62.79±0.74 mg gallic acid equivalents (GAE)/g powder and 30.48±0.32%, respectively. In UAE-NADES, the optimal conditions were choline chloride: lactic acid ratio of 1:4 with a 50% water addition, 20 min extraction (TPC and antioxidant activity of 65.25 mg GAE/g powder and 26.45±0.02%). The Soxhlet and reflux methods gave a TPC of 49.68±0.59 and 50.98±0.54 mg GAE/g powder, and antioxidant activity of 22.87±0.13% and 25.97±0.34%, respectively. Qualitative HPLC analysis showed the presence of quercetin, mahkoside A, 4,6-dihydroxy-4-methoxybenzophenone-2-O-β-D-glucopyranoside, and mangiferin. Conclusion: MAE-ethanol was more efficient than the conventional Soxhlet and reflux methods and performed similarly to UAE-NADES in terms of TPC.